The impact of the training process in functional status and parameters of physical qualities of sportsmen-veterans on stage exit from the sport of higher achievements - Viacheslav Mulyk; Vladimir Perevoznik (Kharkiv State Academy of Physical Culture, 2017)
Purpose: to accomplish the analysis of influence of the training loadings on the indices of the functional state and physical qualities in different age periods of sportsmen-veterans. Material & Methods: researches were conducted with the sportsmen-veterans (football players) of the different age groups (35-40; 41-45; 46-55) who continued to employ and participate in competitions after finishing of active performances in professional commands. The methods of determination of level of motive qualities and indices of the functional state of footballers-veterans were used. Results were calculated by the methods of mathematical statistics. Results: the results of long-term researches of determination of dynamics of changes of motive qualities level and functional state indices during age period 35-55-years of football players are presented. Conclusions: it is determined that during the research period the most changes of level of physical qualities and indices of functional state are received in the period of 35-40 years, that is caused by plummet of the training and competitive loadings after active employments in professional soccer commands.